Limb Lengthening after Primary Total Knee Arthroplasty: Customized Patient-Specific Instrumentation Does Not Affect Expected Limb Lengthening - Christopher Fang; Kenneth McAlpine; Michael Gustin; Ruijia Niu; David Freccero; Matthew Gordon; Eric L. Smith (Advances in Orthopedics)
Introduction. Expectations for limb length differences after TKA are important for patient perception and outcomes. Limb length discrepancies may occur due to postoperative leg length increases, which can lead to decreased patient functionality and satisfaction and even possible litigation. The purpose of this study is to examine the frequency and extent of limb lengthening among various preoperative deformities and between two different implant systems. Methods. Preoperative and postoperative full-length standing radiographs were obtained between August 2018 and August 2019 to measure mechanical axis and limb length of operative limbs. Demographic information such as age, sex, and BMI was also collected. Patients were grouped into categories for pre- and postoperative subgroup analysis: valgus, varus, customized implant, and conventional implant. Regression analysis was performed to evaluate significant relationships. Results. Of the 121 primary TKAs analyzed, 62% of the knees showed an increase in limb length after TKA, with an average lengthening of 5.32 mm. Preoperative varus alignment was associated with a mean lengthening of 3.14 mm, while preoperative valgus alignment was associated with a mean lengthening of 16.2 mm. Overall, there were no statistically significant differences in limb lengths pre- and postoperatively (p = 0.23) and no significant changes in limb length for any subgroup. Further, no variables were associated with limb length changes (p = 0.49), including the use of customized implants (p = 0.2). Conclusions. Limb lengthening after TKA is common and, on average, occurs more significantly in valgus knees. No significant difference in limb lengthening could be demonstrated using customized over conventional implants. Preoperative counseling is important to manage patient expectations.